2003
DOI: 10.1002/cne.10613
|View full text |Cite
|
Sign up to set email alerts
|

Synaptology of trigemino‐ and spinothalamic lamina I terminations in the posterior ventral medial nucleus of the macaque

Abstract: We used the electron microscope to examine lamina I trigemino- and spinothalamic (TSTT) terminations in the posterior part of the ventral medial nucleus (VMpo) of the macaque thalamus. Lamina I terminations were identified by anterograde labeling with biotinylated dextran, and 109 boutons on 38 terminal fibers were closely studied in series of ultrathin sections. Five unlabeled terminal boutons of similar appearance were also examined in detail. Three-dimensional, volume-rendered computer models were reconstru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…Briefly, preceding anatomical evidence indicates that VMpo is a cytoarchitectonically and immunohistochemically distinguishable region in the posterolateral thalamus of monkeys and humans (Craig et al, 1994;Blomqvist et al, 2000;Craig, 2004) that receives dense clusters of lamina I terminal arbors that bear large, glutamatergic boutons organized in triadic arrangements with proximal postsynaptic dendrites and GABAergic presynaptic dendrites (Beggs et al, 2003). Physiological evidence in monkeys indicates that VMpo neurons are organized in clusters that show nociceptive-specific and thermoreceptive-specific responses similar to those of lamina I neurons (Craig et al, 1994(Craig et al, , 1999(Craig et al, , 2001.…”
Section: Distinct Lamina I Stt Projection To Vmpomentioning
confidence: 98%
“…Briefly, preceding anatomical evidence indicates that VMpo is a cytoarchitectonically and immunohistochemically distinguishable region in the posterolateral thalamus of monkeys and humans (Craig et al, 1994;Blomqvist et al, 2000;Craig, 2004) that receives dense clusters of lamina I terminal arbors that bear large, glutamatergic boutons organized in triadic arrangements with proximal postsynaptic dendrites and GABAergic presynaptic dendrites (Beggs et al, 2003). Physiological evidence in monkeys indicates that VMpo neurons are organized in clusters that show nociceptive-specific and thermoreceptive-specific responses similar to those of lamina I neurons (Craig et al, 1994(Craig et al, , 1999(Craig et al, , 2001.…”
Section: Distinct Lamina I Stt Projection To Vmpomentioning
confidence: 98%
“…A projection which does not fit this pattern , from HPC lamina I cells to thalamic nucleus VMpo [28], has been challenged on technical grounds [55;141]. Even though subsequent anatomical studies established the validity of a lamina I projection to VMpo [8;32;97], the classical view persists – i.e., that SI processing of pain occurs in areas 3b and 1. Craig and Blomqvist (2002), for example, viewed the projection from VMpo to area 3a as a “corollary track” subserving sensorimotor integration.…”
Section: Summary and Functional Implications Of Si Encoding Of Painmentioning
confidence: 99%
“…It was named the posterior part of the ventral medial nucleus (VMpo), because together with the contiguous basal part of the ventral medial nucleus (VMb), it constitutes a topographically coherent structure that receives ascending input representative of all interoceptive (homeostatic sensory) activity (Beckstead et al, 1980; Pritchard et al, 2000). The lamina I terminations in VMpo consist of dense clusters of large boutons that are glutamatergic (Blomqvist et al, 1996) and form triadic synaptic complexes characteristic of thalamic relay nuclei (Beggs et al, 2003). Thus, microelectrode recordings that revealed clusters of thermoreceptive-specific (COOL) and nociceptive-specific (NS) neurons in VMpo that are topographically organized with the same antero-posterior gradient (head to foot) naturally suggested that VMpo could serve as a specific relay nucleus for pain and temperature sensations (Craig et al, 1994).…”
Section: Introductionmentioning
confidence: 99%